Critical Success factors for restaurant franchisees in Kenya - Gikonyo, Lucy (Strathmore University, 2014)
In today‟s globalized world, businesses look to expand in order to have a global presence. Restaurant businesses have expanded internationally using franchising. This study seeks to determine the critical success factors of a franchised restaurant system entering the Kenyan market from the franchisees perspective. It seeks to „to establish how franchisees define, identify and evaluate success. This study provides a theoretical framework that helps to understand the background of why organizations seek to expand using franchising method and consequently the critical success factors of franchised restaurants entering the Kenyan market. The study used qualitative methodology in establishing the views of franchisees with the use of in-depth interviews for collecting data. The results yielded critical success factors from the franchisees perspective. These critical success factors from the franchisees point of view include a strong brand identity, good financial management, employee competence, good staff management, overall competent management and relationship marketing. These findings can be used by restaurant franchisees that seek to establish successful businesses in the Kenyan market and other similar regional markets. The Africa franchise partners may also find useful information in setting up the Franchise Association of Kenya. Other franchise businesses may also benefit from some aspects of the study.
Conference paper presented at the 1st African Conference on Sustainable Tourism in Strathmore University, Kenya.
Keywords: Franchising; restaurant franchisees